Analisis Vegetasi Mangrove di Kelurahan Bonkawir Kota Waisai Kabupaten Raja Ampat - Simon Sanadi; Novelina Tampubolon; Nurhani Widiastuti; Fanny Fransina C Simatauw; Marjan Bato; Bernadus Duwit (Fakultas Perikanan dan Ilmu Kelautan, Universitas Papua, 2023)
The high level of land conversion and utilization for wood extraction in the mangrove ecosystem in Bonkawir Village, Raja Ampat Regency impacts environmental degradation. Damage of mangrove ecosystems results in a decrease in the diversity and abundance of fish populations. The lack of scientific information about the current condition of the mangrove ecosystem on the coast of Bonkawir Village is an important reason to conduct a study related to the analysis of mangrove vegetation. This study aimed to identify mangrove species, describe the composition, density, frequency, dominance, and Important Value Index (INP) of mangroves on the coast of Bonkawir Village, Waisai District, Raja Ampat Regency. Data were collected using the line plot transect method at three observation stations then it is analyzed to find out the INP. Based on the observation, it is known that the types of mangroves found at the study site were 14 families consisting of 20 species. Species scattered throughout the station were Rhizopora apiculata, Rhizopora mucronata, Bruguiera gymnorrhiza, Xylocarpus granatum, and Derris trifoliate. The condition of the substrate which is dominated by muddy sand and water quality parameters that affect the growth of mangroves in general still meet the quality standards of mangrove growth. The Rhizopora apiculata had the highest Relative Density, Relative Frequency, and Relative Dominance in the tree category at Stations I and II so it had the highest INP at both stations. The tree category Bruguiera gymnorrhiza has the highest INP at Station III. At Station I the species with the lowest INP was found in Rhizopora mucronata; at Station II was Xylocarpus muloccensis. Meanwhile, Bruguiera parviflora and Ceriops decandra in the tree category together have the lowest INP at Station III.